Measuring competitive balance in Formula One Racing - Oliver Budzinski; Arne Feddersen (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2019)
The Formula One Championship (F1) is one of the biggest sports businesses in the world. But, however, it seems to astonish that only very few scholarly articles analyze the F1 business. The aim of this study is to contribute to closing two gaps in the existing literature: it contributes (1) to the (sports) economic analysis of the F1 business and (2) to the literature on competitive balance in non-team sports. Like competitive balance in team sport leagues, also for F1 racing three dimensions can be distinguished: (a) race-specific competitive balance, (b) within-season competitive balance, and (c) between-season competitive balance. In addition to classical tools and data, some new and F1 specific indicators, like average lead changes or leading distance, are employed. Also, pitfalls induced especially by the used data source or calculation method are highlighted.
Keywords: Z20; Z21; L83; C01; L13; M21; 330; Formula One Motor Racing; competitive balance; empirical industry study; sports economics